2006
DOI: 10.1111/j.1574-695x.2005.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the core oligosaccharide and O-units in the R- and SR-type lipopolysaccharides of reference strains ofPseudomonas aeruginosaO-serogroups

Abstract: Highly phosphorylated core oligosaccharides and those substituted with one O-antigen repeating unit were obtained by mild acid degradation or strong alkaline hydrolysis of lipopolysaccharide samples from 23 reference strains representing all Pseudomonas aeruginosa O-serogroups. Studies by high-resolution electrospray ionization mass spectrometry and two-dimensional NMR spectroscopy revealed both conserved and variable structural features of the lipopolysaccharides of various O-serogroups. The upstream terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 33 publications
3
90
1
Order By: Relevance
“…As expected, the rmlC mutant core OS structure lacked L-Rha residues. The presence of partial acetylation (50 to 70%) of the outer core sugars, such as residue L, found in LPS from rmlC, wapR, and migA rmd knockout strains and the phosphorylation patterns of all strains were consistent with the results described in a previous report (2).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As expected, the rmlC mutant core OS structure lacked L-Rha residues. The presence of partial acetylation (50 to 70%) of the outer core sugars, such as residue L, found in LPS from rmlC, wapR, and migA rmd knockout strains and the phosphorylation patterns of all strains were consistent with the results described in a previous report (2).…”
Section: Discussionsupporting
confidence: 80%
“…The outer core is composed of four D-glucose (D-Glc) residues, one L-rhamnose (L-Rha) residue, and one N-(L-alanyl)-D-galactosamine residue, and its biosynthesis is not fully understood. The structures of the core OS of several different serotypes, clinical isolates, and rough mutants of P. aeruginosa have been reported previously (2,3,12,17,24). The results of the previous studies showed that there are minor variations in phosphate and O-acetyl substituents in some of the core sugars.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The S-type LPS is involved in nonmucoid and in early stage of P. aeruginosa infection in CF patients, whereas the R-type LPS is associated with mucoid and late stage of P. aeruginosa infection in CF patients [139]. The O-antigen is immunogenic in the host for the induction of protective antibodies, whereas lipid A is the core endotoxic component for induction of inlammatory responses [138]. More than 20 serotypes of O-antigens have been identiied [138].…”
Section: Antibody and Vaccine Development Against Lpsmentioning
confidence: 99%
“…LPS has two types, smooth or S-type and rough or R-type. S-type LPS consists of O-polysaccharide (O-antigen) repeats linked with a core-conserved oligosaccharide and a lipid A moiety, while R-type LPS lacks O-antigen and only contains the core oligosaccharide [138]. The S-type LPS is involved in nonmucoid and in early stage of P. aeruginosa infection in CF patients, whereas the R-type LPS is associated with mucoid and late stage of P. aeruginosa infection in CF patients [139].…”
Section: Antibody and Vaccine Development Against Lpsmentioning
confidence: 99%